2014
DOI: 10.1051/0004-6361/201424221
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for buffeting-induced kink waves in solar magnetic elements

Abstract: The role of diffuse photospheric magnetic elements in the energy budget of the upper layers of the Sun's atmosphere has been the recent subject of many studies. This was made possible by the availability of high temporal and spatial resolution observations of the solar photosphere, allowing large numbers of magnetic elements to be tracked to study their dynamics. In this work we exploit a long temporal series of seeing-free magnetograms of the solar photosphere to study the effect of the turbulent convection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
(93 reference statements)
2
28
0
Order By: Relevance
“…Indeed, these authors have shown that compressive and non-compressive waves, cannot only coexist in the same flux tube but that the kink mode can excite a longitudinal density perturbation, whose maximum is reached at the inversion points of the flux tube's horizontal motion. More recently, Stangalini et al (2014) observed the excitation of kink sub-harmonics in small magnetic elements in the solar photosphere. They also noted that sub-harmonics can be considered as the signature of the chaotic excitation of kink waves in strongly non-linear systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these authors have shown that compressive and non-compressive waves, cannot only coexist in the same flux tube but that the kink mode can excite a longitudinal density perturbation, whose maximum is reached at the inversion points of the flux tube's horizontal motion. More recently, Stangalini et al (2014) observed the excitation of kink sub-harmonics in small magnetic elements in the solar photosphere. They also noted that sub-harmonics can be considered as the signature of the chaotic excitation of kink waves in strongly non-linear systems.…”
Section: Discussionmentioning
confidence: 99%
“…This has important implications for the generation of a wide spectrum of viable propagating periodicities in the lower solar atmosphere, particularly if the driving (i.e., buffeting) frequencies are at values that are not necessarily multiples or fractions of the flux tube's natural frequency. Therefore, the work of Stangalini et al [2014] tentatively suggests that a broad spectrum of wave periodicities in small-scale magnetic elements can be generated regardless of the input motions.…”
Section: Kink Wavesmentioning
confidence: 99%
“…Most recently, Stangalini et al [2014] employed a long time series of high-resolution photospheric magnetograms to study the effects of turbulent convection on the excitation of kink oscillations in small-scale magnetic elements. Importantly, the authors utilised empirical mode decomposition techniques, which allowed them to more accurately analyse non-stationary time series which may be dominated by the horizontal displacements of magnetic flux tubes that are continuously advected and dispersed by granular flows.…”
Section: Kink Wavesmentioning
confidence: 99%
“…The EMD technique has already been employed to study kink waves in small-scale magnetic elements and more information about the application of this technique can be found in Stangalini et al (2014).…”
Section: Empirical Mode Decomposition (Emd)mentioning
confidence: 99%